Draft Fourth Five-Year Plan (1969-74) Maharashtra State Part I-Outline - Planning Commission (Planning Commission, 1969)
The State of Maharashtra was formed on May 1, 1960, as a result of the bifurcation of the erstwhile composite State of Bombay. The total area of the State is about 306 lakh sq. kms. and its population according to the Census of 1961, is about 39’6 millions. Both in respect of the area and population the State accounts for a little over 9 percent of the country’s area and population. For administrative purposes, the State is divided in four Divisions the Bombay, Poona, Nagpur and Aurangabad Divisions. The territorial limits of the State are defined by the Arabian Sea to the West, the State of Gujarat to the North-West, the State of Madhya Pradesh to the North and the States of Mysore and Andhra Pradesh to the South and East. It is divided into high and low level tracts by the Western Ghats which run parallel to the coast at an average height of 3,000 to 4,000 feet. The Ghats receive a very high rainfall (100—175 inches) and are densely forested. They also constitute the main water shed of the Deccan, feeding the major east-flowing rivers of Godavari, Krishna and their main tributaries, as well as numerous smaller and shorter West flowing rivers. Between the foot hills and the Arabian Sea lies a narrow strip of rugged land broken by numerous rivers, creeks and isolated ranges of hills. The rainfall in this region varies between 75 and 100 inches per year. The Tapi flows through a valley between the Satpura hills situated along the northern fringe of the State and Ajanta hills which form the northern edge of the plateau. This valley is distinguished from the main plateau by its alluvial soils. Climatically it suffers from being in the rain shadow. Precipitation in this region is low (about 25 inches) in the Western portions but increases to 35 inches in the eastern end of the valley.
Draft Fourth Five-Year Plan (1969-74)
Maharashtra State
Keywords: Development-A Retrospect; Problems of District Planning; Fourth Plan in Outline; A Review of the financial resources of the State; Agriculture; Animal Husbandry; Dairy Development; Forests; Co-operation; Warehousing and Marketing; Health and Family Planning; Water Supply and Sanitation; Urban Development; Regional Planning and Housing; Craftsman Training and Labour Welfare; Miscellaneous Programmes.